Light Sheet Fluorescence Microscopy Illuminating Soft Matter - You, Ruilin; McGorty, Ryan (Frontiers in Physics, 2021)
Volumetric microscopic imaging data acquired at high speeds is often needed in studies of soft matter. Several microscopy techniques exist for this purpose, but a relative newcomer is light sheet fluorescence microscopy (LSFM). This microscopy method has seen spectacular growth in the biological sciences over the past two decades. In this perspective, we highlight how LSFM may also apply to the field of soft matter. We review the principles and recent advances of LSFM and discuss how it has been used in prior soft matter studies. We demonstrate how a recent implementation of LSFM can be used to study capillary wave fluctuations and droplet coalescence in a colloidal fluid system.